Crystallographic studies of coagulation factor XII - Manna, Rosa (2016)
Coagulation Factor XII (FXII) is an important protein involved in the initiation of the intrinsic pathway of the coagulation cascade. Recent studies suggested that FXII may play a role in pathological thrombosis without compromising physiological hemostasis. For this reason, the inhibition of FXII could represent a new and selective strategy for preventing stroke and other thromboembolic diseases. Since there is no structure available for the protease domain of FXII, the knowledge of the overall domain structure can be significantly helpful in the development of inhibitors with specific selectivity for the target.